Hubungan dukungan keluarga terhadap kepatuhan ibu hamil dengan hiv dalam mengkonsumsi ARV - Prasetyo, Taruna (Jurnal Keperawatan Muhammadiyah, 2024)
HIV/AIDS is a phenomenon with the reported number being higher than the actual number, 90% of babies are infected with HIV from their mothers from pregnancy to breastfeeding. Antiretroviral therapy (ARV) slows down and suppresses the growth of the HIV/AIDS virus so that the quality of life of PLWHA is better. One of the important factors for PLWHA is family support in compliance with ARV treatment. The purpose of the research is to find out the relationship between family support and the compliance of pregnant women with HIV in taking ARVs. The research used a purposive sampling technique with a total of 30 respondents. Cross sectional research design, Spearman statistical test. The results of the research show that most of the respondents are 26-45 years old as many as 23 respondents (76.7%), have high school education as many as 21 respondents (70%) and as housewives as many as 21 respondents or 70%. There is a relationship between family support in pregnant women with HIV in consuming ARVs, p value 0.004. Good family support in pregnant women with HIV has a better level of compliance in consuming ARVs compared to pregnant women with poor family support. Compliance with therapy and other support systems has a large role in improving the quality of life of patients with HIV/AIDS and reducing morbidity and mortality rates. mortality of pregnant women with HIV.